2004
DOI: 10.1529/biophysj.103.034991
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cells and Tissues with Refractive Index Radiology

Abstract: Can individual cells, including live cells, be imaged using hard x rays? Common wisdom until now required sophisticated staining techniques for this task. We show instead that individual cells and cell details can be detected in culture solution and tissues with no staining and no other contrast-enhancing preparation. The sample examined can be much thicker than for many other microscopy techniques without sacrificing the capability to resolve cells. The key factor in our approach is the use of a coherent sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 19 publications
1
58
1
Order By: Relevance
“…Hwu's report demonstrated that the volume rendered 3D structure of the aorta could differentiate the individual cells [4]. However, the 3 D images in the present study were not yet at the same level as optical microscopy, with some blurring.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Hwu's report demonstrated that the volume rendered 3D structure of the aorta could differentiate the individual cells [4]. However, the 3 D images in the present study were not yet at the same level as optical microscopy, with some blurring.…”
Section: Discussioncontrasting
confidence: 60%
“…The present results are based on the differences in the refractive index, which enhance the conventional absorption contrast by X-ray sources with high coherence, which produces a sharp enhancement of the edge in the image [4]. As the previous report, a synchrotron X-ray used in the present study had unmonochromatic synchrotron beams and a simple detector system, differently from other synchrotron radiation systems, to implement this type of edge enhancement and to image extremely fine details [7].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Individual neurons and fibroblasts could be identified within thin collagen gels in the absence of any exogenous contrast using propagation-based PC imaging. 56,62 Propagation-based CT has also been shown to allow the identification of single chondrocytes within cartilage lacuna. The volume of a single cell could be used to estimate cell density within a region of articular cartilage from CT images.…”
mentioning
confidence: 99%